Testament katyńskiej sieroty - SIESTRZEWITOWSKA, Klaudia (Historia i Świat, 2015)
The will of the Katyn orphan - The work was awarded the first prize in the competition commemorating "75th anniversary of the Katyn Massacre. Reflections of a contemporary teenager" announced by the Institute of History and International Relations of the University of Natural Sciences and Humanities in Siedlce.